Analisis Utang Piutang Emas di Desa Laban Menganti Gresik - Isnaini, Dwi; Suryaningsih, Sri Abidah (Universitas Negeri Surabaya, 2019)
This study aims to determine practice the gold debts in Laban Village in terms of Islamic law. The qualitative method was used in this study with descriptive approach. The subjects in this study were the giver and recipient of the gold debts. The analysis technique was used the field data analysis of the Miles and Hubberman models in this research. The result of the study was showed that the implementation of the gold debts in Laban village was still often carried out, this was due to the ease in filing debt. The gold debts in Laban village did not use any contract agreement in making initial agreements. The practice of gold debts in Laban village still contains elements of riba qardh which were come from an addition proportional to the value of the debt proposed, especially in taking additional items that were not accompanied by an agreement with the recipient of the debt. The solution to avoid gold debts from riba by relying debt with a formidable sale and purchase contract, therefore, that was allowed to take profits (margin).